2023
DOI: 10.2196/46629
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-Measured Inpatient Physical Activity and Associated Outcomes After Major Abdominal Surgery: Systematic Review

Abstract: Background It remains unclear how inpatient physical activity after major abdominal surgery affects outcomes. Accelerometer research may provide further evidence for postoperative mobilization. Objective We aimed to summarize the current literature evaluating the impact of accelerometer-measured postoperative physical activity on outcomes after major abdominal surgery. Methods We searched PubMed and Google S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…13 In a recent systematic review, Fuchita et al identified 6 RCTs that evaluated FT-based interventions for mobilization after surgery. 38 In line with our results, none of the trials showed improvement in postoperative complications using fitness tracker-based interventions. However, in contrast to EXPELLIARMUS, none of these studies evaluated postoperative morbidity as a primary outcome parameter.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…13 In a recent systematic review, Fuchita et al identified 6 RCTs that evaluated FT-based interventions for mobilization after surgery. 38 In line with our results, none of the trials showed improvement in postoperative complications using fitness tracker-based interventions. However, in contrast to EXPELLIARMUS, none of these studies evaluated postoperative morbidity as a primary outcome parameter.…”
Section: Discussionsupporting
confidence: 85%
“…18,21,[39][40][41] In addition, all but one of the previous studies exhibited a major risk of bias; most were single-center trials and significantly smaller (< 110 patients) than EXPELLIARMUS. 38 In addition, contrary to previous trials, EXPELLIARMUS evaluated a wide range of recovery parameters, patient-reported outcome measures, and FT data to cover the entire spectrum of postoperative recovery. 30 However, none of these outcomes showed clinically relevant improvement in the experimental group.…”
Section: Discussionmentioning
confidence: 99%